SERIE: ECONOMÍA APLICADA A LA INGENIERÍA DE PROCESOS (Parte 1) ESTIMACIÓN COSTO DEL PRODUCTO - Porlles Loarte, José (2004)
In the first part of this paper we revise the fundamentals of model and thecniques applied to economics analysis of process engineering.